Characteristics of Lung Microbiota in Children’s Refractory Mycoplasma pneumoniae Pneumonia Coinfected with Human Adenovirus B - Wenxiang Zhou; Jinglong Chen; Zhimin Xi; Yanyan Shi; Libo Wang; Aizhen Lu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Both M. pneumoniae and human adenovirus (HAdV) are common causative agents of lower respiratory tract infection in children; nonetheless, the lung microbiota in patients with coinfection of HAdV and M. pneumoniae remain unexplored. Methods. Thirty-two children, diagnosed with refractory M. pneumoniae pneumonia (RMPP), entered into the one-year study from July 1, 2019 to June 30, 2020. Among them, twenty-one entered into the M. pneumoniae monoinfection (MP) group and eleven entered into the M. pneumoniae and HAdV coinfection (MP&ADV) group. The characteristics of the clinical findings were examined, and the lung microbiota was analyzed by metagenomic next generation sequencing (mNGS). Results. Eleven patients in the MP&ADV group were coinfected with human mastadenovirus species B. The fever days lasted for significantly longer periods in the MP&ADV group than in the MP group (P<0.05). The percentage of CD16+CD56+ cells was significantly higher in the MP&ADV group than that in the MP group (P<0.05). There were no significant differences in α-diversity between the MP and MP&ADV groups, but the β-diversity was clearly higher in the MP&ADV group than that in the MP group (P<0.05). At the microbial level, the top phylum of the MP BALF microbiota was Tenericutes; in contrast, it was Preplasmiviricota in the MP&ADV BALF. There were significant differences in the relative abundance of Tenericutes and Preplasmiviricota between the two groups (P<0.001). There was a strong positive correlation between human mastadenovirus B and fever days, M. pneumoniae and level of IgA, and a strong negative correlation between Mycoplasma pneumoniae and PCT. Conclusions. In RMPP, the BALF microbiota in children with mono M. pneumoniae infection was simpler than those with coinfection with human mastadenovirus B. Prolonged fever days were associated with human mastadenovirus B coinfection.